2022
DOI: 10.12998/wjcc.v10.i32.11835
|View full text |Cite
|
Sign up to set email alerts
|

Neck pain and absence of cranial nerve symptom are clues of cervical myelopathy mimicking stroke: Two case reports

Abstract: BACKGROUND Cervical myelopathy is a potential stroke imitator, for which intravenous thrombolysis would be catastrophic. CASE SUMMARY We herein present two cases of cervical myelopathy. The first patient presented with acute onset of right hemiparesis and urinary incontinence, and the second patient presented with sudden-onset right leg monoplegia. The initial diagnoses for both of them were ischemic stroke. However, both of them lacked cranial nerve symptom and suffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The patient was then transferred to us due to suspicion of a cervical epidural hematoma. Since the distribution of hematoma varies from side to side, hemiplegia and Brown‐Séquard syndrome‐like symptoms may occur; differentiation from cerebral infarction is particularly important 11 . In this case, the hematoma was located slightly to the right posterior to the spinal cord, and there was no association between the location of the hematoma and neurologic symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…The patient was then transferred to us due to suspicion of a cervical epidural hematoma. Since the distribution of hematoma varies from side to side, hemiplegia and Brown‐Séquard syndrome‐like symptoms may occur; differentiation from cerebral infarction is particularly important 11 . In this case, the hematoma was located slightly to the right posterior to the spinal cord, and there was no association between the location of the hematoma and neurologic symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…The onset of neck or back pain and the absence of cranial nerve signs have been suggested as important indicators for diagnosing cervical spinal epidural hematoma with hemiparesis [ 6 , 9 , 10 ]. However, a recent review found that 16 out of 51 cases presented with hemiplegia without neck pain, and 6 out of 51 cases presented with hemiplegia and dysarthria [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typical symptoms of cervical epidural hematoma with hemiparesis are neck pain and absence of cranial nerve symptoms [ 6 , 9 , 10 ]. These symptoms are similar to hemorrhagic stroke, including subarachnoid hemorrhage, and ischemic stroke, including arterial dissection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations